Implementation of Village Funds for Infrastructure Development in Nafri Village, Abepura District, and Jayapura City - Terianus L. Safkaur (Journal of Social Science)
The Jokowi government is implementing infrastructure development policies as a form of seriousness in developing society from village to city level (Bottom Up - Top Down). Through budget allocations such as PNPM Mandiri/DANA DESA, the government provides space for the community to participate in development. In Jayapura City, Papua Province, Village Funds and Prospect Funds (sourced from OTSUS) are used to finance strategic village development programs. The research results show that Nafri Village in the Abepura District of Jayapura City is able to manage funding sources, including Village Funds and Village Funds from the Jayapura City APBD. In 2022-2023, this village will carry out various infrastructure activities such as road construction, construction of a people's market, toilets and renovation of the village hall office. Thus, the implementation of Village Funds and Prospect Funds has made a positive contribution to infrastructure development, economic empowerment and strengthening village institutional capacity.